Perlawanan Pihak Ketiga Pemegang Sertifikat Hak Pakai Atas Sita Eksekusi Tanah Sriwedari - Azmi Hawari Sunny; Artaji Artaji; Betty Rubiati (Universitas Widya Gama Malang, 2023)
Third party resistance according to Article 195 Paragraph (6) of HIR regulate the legal standing of the applicant party, namely based on rights of ownership. However, the Surakarta City Government filed a third party resistance based on the ownership of Right of Use. Therefore, this research aims to analyze the resistance of third party filed based in the ownership of Right of Use and the settlement of Sriwedari land dispute. This research is based on a normative juridical approach and then analyzed by qualitative juridical methods. The result of the research shows that a third party resistance based on the ownership of rights other than rights of ownership can be accepted as the legal standing of the party. However, the legal standing of the Surakarta City Government as applicant of third party resistance was not met subjective requirements. Futhermore, Sriwedari land disputes can be resolved through non-litigation dispute resolution by negotiation or mediation. Using this dispute resolutions, the parties obtain legal certainty in resolving Sriwedari disputes without any party feel defeated, minimize losses and social impacts.